Etnomatematika: Eksplorasi Budaya Sasak sebagai Sumber Belajar Matematika Sekolah Dasar - Asri Fauzi; Aisa Nikmah Rahmatih; Muhammad Sobri; Radiusman Radiusman; Arif Widodo (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2020)
The purpose of this research is to describe the results of the exploration of ethnomathematics of Sasak culture that can be used as a source of learning mathematics. This type of research is exploratory qualitative research with an ethnographic approach. This research focuses on buildings, crafts, arts, and traditional snacks. The research instrument is the researcher himself. While the method of data collection by interview, field studies, and documentation. Data analysis techniques with triangulation are data reduction, data presentation, and drawing conclusions. The results showed that Sasak cultural products can be used as a source of learning mathematics, especially on the elements of geometry including rectangles, triangles, trapezoid, circles, rhombus, laying-kites, cones, cylinders, and pyramid. Learning resources derived from Sasak culture, if properly utilized, will create meaningful mathematics learning for students.